Pendekatan Analitik untuk Menduga Koefisien Pindah Panas Konveksi - Ida Bagus Putu Gunadnya; Kamaruddin Abdullah; Armansyah Halomoan Tambunan (PERTETA, 2008)
Convective heat transfer coefficient has an important role in thermal processes. It is commonly determined and formulated using empirical models, while some workers have also proposed formulas based on analytical methods. This paper describes the formulation of convective heat transfer coefficient using an analytical approach which could be expressed as h = 5.277 V0.5Keywords: convective heat transfer coefficient, analytical approach Diterima: 11 Juni 2007; Disetujui: 24 September 2007